FUNCTIONAL PRODUCT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes the concepts of function derivatives, Focus on teaching and learning using advanced pedagogical technologies in a practical lesson. The key to pedagogical technology is to achieve clearly defined goals